Knowledge of and interest in opioid overdose education and naloxone distribution among US veterans on chronic opioids for addiction or pain. (3rd July 2016) - Tiffany, Elizabeth; Wilder, Christine M.; Miller, Shannon C.; Winhusen, Theresa
Abstract: Aims : The Veterans Health Administration (VHA) is implementing opioid overdose (OOD) education and naloxone distribution to reduce rising rates of OOD deaths. This study assessed knowledge and interest in OOD prevention with naloxone at a VHA hospital where naloxone kits were not yet available. Methods : Veterans receiving opioids for ≥3 months, including 52 from the Opioid Substitution Clinic (OSC) and 38 from the Pain Management Clinic (PMC), were interviewed about their attitudes and experience with OOD and naloxone. Findings : 52% of OSC and 21% of PMC veterans reported having ever experienced an OOD. Less than half had heard of naloxone and none owned a naloxone kit. After a brief explanation, 73% of OSC and 55% of PMC veterans reported wanting a kit. Veterans who reported wanting a kit were more likely to have witnessed ( p  < 0.001) and/or experienced ( p  < 0.001) an OOD and were more likely to have used intravenous drugs in their lifetimes ( p  < 0.05). Conclusions : Participants were not well informed about naloxone but many OSC veterans had a history of OOD and were interested in having a naloxone kit. There was also a subgroup of veterans prescribed opioids for chronic pain who had a history of OOD and were interested in naloxone.